2018
DOI: 10.7324/rjc.2018.1112008
|View full text |Cite
|
Sign up to set email alerts
|

"BIOSORPTION OF COPPER (II) ON TO THE WASTE LEAVES OF KAFAL (Myrica esculenta) "

Abstract: The commonly used removal processes for heavy metals from contaminated wastewater and cited in the literature are chemical precipitation, electrowinning, carbon adsorption, reverse osmosis, preconcentrations, biosorption, phytoremediation etc. Among these, biosorption is comparatively efficient, low cost, economical and reliable process. Actually, the reliability of the process is depending on the choice of local biosorbents and their abundant availability. The waste plant leaves of Kafal were collected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Earlier literature has reported that the value of 1/n between 0.1-0.5 indicates good adsorption, 0.5-1.0 indicates moderate adsorption and 1/n > 1 indicate the possibility of weak adsorption. 24 Temkin isotherm illustrates the distribution of adsorbate on the adsorbent surface as the function of binding energy. 25 The Temkin plot of lnCe vs. qe (…”
Section: Isotherm Studiesmentioning
confidence: 99%
“…Earlier literature has reported that the value of 1/n between 0.1-0.5 indicates good adsorption, 0.5-1.0 indicates moderate adsorption and 1/n > 1 indicate the possibility of weak adsorption. 24 Temkin isotherm illustrates the distribution of adsorbate on the adsorbent surface as the function of binding energy. 25 The Temkin plot of lnCe vs. qe (…”
Section: Isotherm Studiesmentioning
confidence: 99%
“…Absorption is one of the methods that commonly used to handle this issue. 3,6,7 For this purpose, a fixed bed system with Ca(OH) 2 sorbent is promising because of its simple structure, the ease of maintenance, the low running cost, and the absence of slurry treatment. However, there are also some drawbacks such as conversion and removal efficiency of gas that is relatively low.…”
Section: Introductionmentioning
confidence: 99%